AB0082 Effects of Anti-Tnf Therapy on Circulating Oxldl-Beta2Gpi Complex Levels in Arthritis. (9th June 2015) - Pusztai, A.; Végh, E.; Váncsa, A.; Bodnár, N.; Szamosi, S.; Nagy, G.; Szöllösi, I.; Csomor, P.; Lopez, L.R.; Matsuura, E.; Szücs, G.; Szántό, S.; et al.
Abstract : Background: Accelerated atherosclerosis, increased cardiovascular (CV) morbidity and mortality have been associated with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Oxidized LDL (oxLDL) and beta 2 glycoprotein I (beta2gpI) antigens have been implicated in atherosclerosis, as well as antiphospholipid syndrome. High circulating oxLDL/beta2gpI levels may reflect vascular damage in acute coronary, syndrome, SLE, and other autoimmune diseases. However, the role of these complexes in RA and AS has not yet been evaluated in relation to therapy. Objectives: Circulating complex levels, as well as the effects of anti-TNF therapy on these complexes were assessed in RA and AS patients. Complex levels were also correlated with various autoimmune-innflammatory and metabolic markers. Methods: Altogether 43 arthritis patients including 30 RA patients treated with either etanercept (ETN) or certolizumab pegol (CZP) and 13 AS patients treated with ETN were included in a 12-month follow-up study. Circulating oxLDL/beta2gpI complexes were assessed by an AtherOx® ELISA system (Corgenix). In addition, disease activity (DAS28 or BASDAI), CRP, IgM rheumatoid factor, anti-CCP, and lipid levels (total cholesterol, TC; LDL-C, HDL-C and triglyceride) were also assessed. Assessments were performed at baseline, as well as 6 and 12 months after treatment initiation. Results: Anti-TNF treatment was highly effective in both diseases, as the mean DAS28 decreased from 6.32 to 3.16 (p=0.02) in RA, mean BASDAI decreased from 5.87 to 1.84 (p<0.001) in AS. In RA, AS and the mixed arthritis population (n=43) baseline oxLDL/beta2gpI levels were 0.235±0.1, 0.245±0.1 and 0.238±0.1, respectively. There were no significant differences between RA and AS patients. In RA, ETN/CZP treatment resulted in non-significant decreases in complex levels after 6 months (0.214±0.1) and 12 months (0.206±0.1). In AS, oxLDL/beta2gpI complex levels did not change after 6 months of ETN therapy, but significantly decreased after one year (0.195±0.1; p=0.01). In the RA+AS population, anti-TNF treatment significantly decreased oxLDL/beta2gpI levelés after 12 months (0.203±0.1, p=0.02). In addition, baseline oxLDL/beta2gpI complex levels positively correlated with TC (RA: r=0.563, p=0.002; AS: r=0.542, p=0.049; RA+AS: r=0.532, p<0.001), and LDL-C (RA: r=0.630, p<0.001; AS: r=0.756, p=0.004; RA+AS: r=0.648, p<0.001) in both diseases. Circulating oxLDL/beta2gpI levels did not correlate with DAS28, BASDAI or CRP. Conclusions: In a mixed cohort of RA and AS patients, anti-TNF therapy suppressed the circulating levels of oxLDL/beta2gpI complexes, markers of atherosclerosis and vascular disease in SLE or APS. Moreover, oxLDL/beta2gpI levels correlated with TC and LDL-C in arthritides. oxLDL/beta2gpI complexes do not seem to be markers of disease activity in RA or AS. Disclosure of Interest: None declared